2018
DOI: 10.1016/j.bja.2018.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow index as an indicator of successful sciatic nerve block: a prospective observational study using laser speckle contrast imaging

Abstract: NCT03169517.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These change rates of SWV N and SWV NMR showing higher diagnostic abilities may be attributed to further normalization of the differences in SWVs between individuals compared with the actual SWV N and SWV NMR values through ratio calculations before and after nerve block This speculation is strongly supported by the results that the CV values of the change rates of SWV N and SWV NMR were lower than those of the respective actual measurements. Similar to our results, the ndings of a previous study demonstrated that the relative change rate of the peripheral blood ow index from the baseline values has a higher diagnostic ability than actual values in determining the effect of the peripheral nerve block because of the large individual variation in baseline value 47 . Collectively, it is suggested that evaluating the ratio of SWV values of nerve to muscle and change rate in the SWV value, rather than measuring the actual SWV value itself, is an important factor for assessing nerve block success.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These change rates of SWV N and SWV NMR showing higher diagnostic abilities may be attributed to further normalization of the differences in SWVs between individuals compared with the actual SWV N and SWV NMR values through ratio calculations before and after nerve block This speculation is strongly supported by the results that the CV values of the change rates of SWV N and SWV NMR were lower than those of the respective actual measurements. Similar to our results, the ndings of a previous study demonstrated that the relative change rate of the peripheral blood ow index from the baseline values has a higher diagnostic ability than actual values in determining the effect of the peripheral nerve block because of the large individual variation in baseline value 47 . Collectively, it is suggested that evaluating the ratio of SWV values of nerve to muscle and change rate in the SWV value, rather than measuring the actual SWV value itself, is an important factor for assessing nerve block success.…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy between these studies and our present results may be explained by differences in the measurement methods used. In previous studies, nerve blood ow was directly measured adjacent to the target nerve using a laser Doppler owmeter 47 , which theoretically has a higher detection sensitivity of blood ow compared to SMI. We speculate that the change in the nerve blood ow induced by the local anesthetic is very faint and lower than the detection sensitivity of SMI, and as a result, the SMI failed to identify this blood ow change in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to our previous study, the LSCI technique could be employed to predict the effect of sciatic nerve block in clinical practice. 16 But the application of this technique in the upper limb needs to be confirmed since the composition and distribution of vascular nerves in upper or lower extremities differ. 14 The BFI value got the biggest rise after the C7 nerve root block in the innervated area (nail bed of the middle finger), which was similar to the one after C6 nerve root block in the innervated area (nail bed of the index finger).…”
Section: Discussionmentioning
confidence: 99%
“…22 As we have previously reported, the BFI values of toes were significantly increased after successful sciatic nerve block. 20 Therefore, the nail bed of each toe was chosen as region of interests in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Our previous study demonstrated that LSCI might be an early, objective, quantitative, and reliable indicator of successful sciatic block. 20 The primary aim of this study was to investigate blood flow changes after lumbar plexus block using LSCI technique.…”
Section: Introductionmentioning
confidence: 99%